Frequency of Indications for Transthoracic Echocardiography (Tte) in Non-Cardiac Patients in Peshawar, Pakistan - Muhammad Tariq Mehr; Muhammad Ishfaq (Gandhara University, 2024)
OBJECTIVES This study aimed to find the frequency of indications for Transthoracic echocardiography and its impact on non-cardiac patient management in Peshawar, Pakistan. METHODOLOGY A cross-sectional study was conducted in Medical B Ward, Department of Internal Medicine at Hayatabad Medical Complex, Peshawar, Pakistan, over six months from July to 31st December 2020. A non-consecutive probability sampling technique was used. The sample size was calculated using an Openepi calculator, keeping 25.9 % as the frequency of requesting heart failure as an indication of echocardiography, 6.15 % as the confidence limit, and 95 % as a confidence interval. RESULTS A total of 195 patients were included in the study. The mean age of the patients was 483 years, with 59% females and 41% males. The major indication for TTE was assessing left ventricular systolic function in 146 (75%) patients and then finding the cause of the observed arrhythmias in 15 (7.5%) patients. A major proportion (95%) of the evaluated patients had no major change in the ongoing management plan following TTE. The working diagnosis in evaluated patients was changed by 12.7%, whereas new management plans were devised in only 4.9% of the cases. CONCLUSION Designing a randomized study to fully elaborate on the utility of TTE in patients admitted to acute medical wards while trying to address all confounding variables is an extremely difficult task.